(untitled) (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2023)
This essay aims to explore the interrelation of the widespread use of digital epitextual material and the common practice, in post-postmodern U.S. fiction, to employ characters and character-narrators that share some biographical details with their authors. Specifically, this essay attends to narrative communication when an autobiographical connection between authors and characters is established not textually, but paratextually, through digital epitexts to be found, for instance, on authors’ social media profiles. Through the analysis of Raven Leilani’s Luster (2020), I will show how digital epitexts acquire a central role for contemporary narrative dynamics: it is through them that many novels realize the author-character connection providing fiction with a layer of alleged authenticity meant to reinforce the post-postmodern tendency to earnestly engage with ethical and political issues.